Places of curriculum making narrative inquiries into children's lives in motion - Huber, Janice; Murphy, M. Shaun; Clandinin, D. Jean; Kükner, Jennifer Lisa Mitton; Orr, Anne Murray (Advances in research on teaching, 2011)
This book documents a radical shift in thinking from focusing on the school as the place where curriculum is made to realizing the ways children and families are engaged as curriculum makers in homes, in communities, and in the spaces in-between, outside of school. The narrative inquiry framing this book investigates the tensions experienced by teachers, children and families as they make curriculum attentive to lives. It draws on a research project involving multi-perspectival narrative inquiries spanning four research sites and traces the tensions experienced by children, families and teachers in multiple curriculum making sites and some of the profound identity making and assessment making implications that become visible. Its attention to the relational in narrative inquiry is focused on tensions that shape lives and, as well, the unfolding of narrative inquiries. This informative book has a wide reaching audience of educational researchers, teacher educators, research methodologists, particularly those interested in narrative inquiry, curriculum scholars, graduate students, university faculty, teachers, administrators and parents alike.